Income inequality in phezukomkhono mlimi farming households: A case study of Nkomazi Local Municipality, South Africa - Sambo, Themba Andries; Oguttu, James W; Mbombo-Dweba, Tulisiwe P (Asian Journal of Agriculture and Rural Development, 2025)
The South African government has developed several policies and intervention programmes to address food insecurity, poverty, and income inequality. One such programme is the Phezukomkhono Mlimi (PKM) initiative. However, empirical evidence demonstrating the impact of government programmes like the PKM on poverty and income inequality remains limited. This study examined income inequality and its determinants. A structured questionnaire was used to collect data from 230 respondents. The data were analyzed using descriptive statistics, the Gini coefficient, and a quantile regression model. The results indicated a high level of income inequality, with a Gini coefficient of 0.48. The majority (60.87%) of households derived their income from farming activities. Other sources of income included retirement funds (10.43%) and salaries (7.39%). The findings suggested a high unemployment rate within the study population. Age, education, household size, and farm size were identified as determinants of income inequality in the study area. Although the income inequality observed was lower than provincial and national levels, government intervention through the PKM programme has not significantly impacted income inequality in the study area. Considering this, policy interventions to improve equitable access to education, family planning, and farm size are recommended.